Experience of family health strategy users about integrative community therapy (Revista Contexto & Saúde, 2023)
To describe the experience of users of the Family Health Strategy regarding Integrative Community Therapy. This study has a qualitative approach. The research consisted of 14 participants and users who actively participated in the referred therapy were elected as members of this study. The location chosen for this study was the municipality of Jequié, located in Bahia. The course of data analysis was guided by the field diary and Bardin's Thematic Content Analysis. From the analysis, five categories emerged, namely: the users' perception of Integrative Community Therapy; Integrative Community Therapy as a light social technology for the promotion of health and social well-being; Integrative Community Therapy as an improvement in lifestyle; Integrative Community Therapy as a new resource in the practice of care; Integrative Community Therapy: an intervention strategy in mental health. In this way, we affirm that Integrative Community Therapy as a listening space is a valuable device to enhance socialization, solidarity and humanization between health workers and users of the Family Health Strategy, thus confirming the central argument investigated in this research.
Keywords: Family Health Strategy; Complementary Therapies; Nursing